Behavior of steel-reinforced concrete-filled square steel tubular stub columns under axial loading. (October 2017) - Ding, Fa-xing; Zhang, Tao; Liu, Xue-mei; Lu, Zhao-Hui; Guo, Qiang; Jiang, Guo-shuai
Abstract: The objectives of this paper is to investigate the mechanical behavior of steel reinforced concrete-filled square steel tubular (SRCFT) stub columns under axial loading through combined experimental and numerical studies. In total of six specimens are tested to investigate the effect of the concrete strength and steel ratio on the mechanical behavior of SRCFT stub columns. The ultimate bearing capacity, ductility, and confinement effects are discussed and clarified based on the experimental results. The inserted steel section can effectively prevent shear cracks in the core concrete from propagating quickly. The strength-weight-ratio of SRCFT stub column is larger than SCFT stub column. In addition, ABAQUS is used to establish the 3D finite element (FE) model and analyze the composite action of SRCFT stub columns under axial loading. Based on the experimental and numerical results, a simplified formula is proposed to estimate the ultimate bearing capacity of SRCFT stub columns using superposition method. The predicted results show satisfactory agreement with both experimental and FE results. Highlights: The column is a steel reinforced concrete-filled squaresteel tubular (SRCFT) stub column. A 3D FE model is developed to analyze the compressive properties of SRCFT stub column. There exists a significant composite action between the steel tube, core concrete and steel section. A practical formula for SRCFT stub columns is proposed.